2020
DOI: 10.34190/jbrm.18.2.003
|View full text |Cite
|
Sign up to set email alerts
|

Business School Teaching of Research Methods – A Review of Literature and Initial Data Collection for Undergraduate Business School Students

Abstract: This paper reviews approaches to teaching research methods and the effectiveness of the student supervisor relationship in managing research projects. Corporate scandal, changes in society, the emergence of online technologies and a need to reduce teaching costs have all led business schools to change their curriculum including how research methods are taught and undergraduate and postgraduate projects supervised. Management research, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This paper continues recent research Mitchell andRich, (2019, 2020), with a review of literature on the teaching of research methods and the quality and effectiveness of the student supervisor relationship in managing research projects conducted by students. Data has been collected at a London based Business School through surveys, focus groups and interviews from undergraduate students as well as faculty and staff.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This paper continues recent research Mitchell andRich, (2019, 2020), with a review of literature on the teaching of research methods and the quality and effectiveness of the student supervisor relationship in managing research projects conducted by students. Data has been collected at a London based Business School through surveys, focus groups and interviews from undergraduate students as well as faculty and staff.…”
Section: Introductionmentioning
confidence: 54%
“…Business schools have experienced a number of changes in response to competition, pressures to revise curriculums, recruitment and a major shift to eLearning and self-managed learning, Mitchell and Rich (2020); www.ejbrm.com 105 ISSN 1477-7029 pedagogy and evaluation, Brown and Rich (2020). In the year 2020 these pressures have been exacerbated by the onset of the Coronavirus pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…These concepts were: presence; flow; mastery; focus; awareness; timelessness; transcendence; unknowing; openness; contact; expressivity; receptivity In the event, I found that I rarely used the sensitising concepts beyond my initial interviews, because each interviewee was able to explore the term "presence" without recourse to another concept. I also found that unstructured "intensive interviews" (Charmaz, 2014) were most productive in terms of codes if I offered largely nondirective listening and empathic responding during the interview (Carmichael & Cunningham, 2017).…”
Section: Research Method-data Gatheringmentioning
confidence: 99%
“…In GT, knowledgeable participants are deliberately selected, not to provide a large general sample of a population, but because they can contribute significant and specific expertise . For this reason, sample sizes in GT tend to be small (Carmichael & Cunningham, 2017). It made sense to me, at least initially, to speak to those people who had both a professional art practice and a professional therapeutic practice.…”
Section: Research Method-data Gatheringmentioning
confidence: 99%
“…Similarly, our experience of teaching research methods and supervising students in preparing dissertations has revealed a wide range of ability, enthusiasm and interest. More recently a growing level of disinterest in undertaking a project and learning research skills has become apparent (Brown and Rich, 2020;Mitchell andRich, 2020, Mitchell andRich, 2021). The popularity and recent growth in eBusiness may mean that assumptions underpinning a traditional Business School curriculum cease or are at least challenged.…”
Section: Introduction 11 Why Do Students Find It a Challenge?mentioning
confidence: 99%